1994
DOI: 10.2169/internalmedicine.33.536
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Infection due to Mycobacterium xenopi.

Abstract: Wedescribe two cases of pulmonary infection due to Mycobacteriumxenopi (M. xenopi). Both cases were men, ages 61 and 54 yr. In the first patient, lung infection due toAf. xenopi occurred after gastrectomy. The second patient had an inactive M. tuberculosis infection. Both had pulmonary symptoms including cough, sputum and fever. Each chest X-ray showed an infiltrative shadow with a cavity in a unilateral, upper lobe. Isolates from both patients were studied not only by microbiological characteristics but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Chemotherapeutic combination protocols with three to four drugs and an overall treatment duration of 18 -24 months usually are recommended in cases of M. xenopi infection [1,5,[12][13][14][15][16]. On the basis of results of vitro susceptibility testing, we selected a combination of clarithromycin, rifabutin, and sparfloxacin for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic combination protocols with three to four drugs and an overall treatment duration of 18 -24 months usually are recommended in cases of M. xenopi infection [1,5,[12][13][14][15][16]. On the basis of results of vitro susceptibility testing, we selected a combination of clarithromycin, rifabutin, and sparfloxacin for therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, Terashima et al 23 reported two cases of pulmonary disease caused by M. xenopi -one occurred after gastrectomy and the other synchronously with M. tuberculosis infection, both presented with features of an infectious disease and unilateral cavitary lesion at chest x-rays 23 . Several cases of Japanese authors have been reported thereafter 22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other species recovered with relative frequency are M. xenopi and M. malmoense which primarily cause pulmonary disease and lymphadenitis, respectively [9,10]. In addition, due to improved culture techniques and the more wide-spread use of 16SrRNA-sequencing for diagnostic purposes [11], an increasing number of previously unrecognized species have recently been identified from clinical sources.…”
Section: Introductionmentioning
confidence: 99%